Sourcing: Which varicose vein is relevant to the ulcer? - Niemer, M.; Miesel, A.; Kahle, B. (Phlebologie, 2014)
Sourcing allowed the small saphenous vein to be identified as the relevant varicose vein in a 41-year-old patient with a pretibial ulcer. Foam sclerotherapy was carried out, reducing the size of the ulcer within a week.
Keywords: CVI; venous ulcer; sourcing; foam sclerotherapy; relevant to ulcer